Anti-fungal Activity of Dalbergia retusa Extract on Gloeophyllum trabeum - Lv, Huangfei; Wang, Yulong; Qu, Mingxuan; Zhang, Yingying; Song, Zhiru; Su, Xingyu; Xu, Bin (Frontiers in Plant Science, 2022)
Hongmu is a type of material with strong corrosion resistance, and its extract has wood preservative properties in a variety of environmental settings. Herein, the processing residue of Dalbergia retusa was used to obtain an ethanol-extract, whose anti-fungal properties and anti-fungal mechanism was investigated with multi-omics principles and gas chromatography-mass spectrometry (GC-MS). The results show that D. retusa extract had a strong inhibitory effect on decaying fungus, and the inhibitory effect was dose dependent. High-throughput sequencing was performed and detected a total of 11,755 genes for transcriptome comparison. A total of 390 genes were differentially expressed, with 69 up-regulated and 321 down-regulated genes, indicating that D. retusa extract can significantly affect metabolic processes in decaying fungus. GC-MS results revealed that D. retusa extract was rich in phenols, ketones, amines, and aromatic compounds, which are likely to contribute to the excellent synergy between anti-fungal properties and anti-fungal activity. In summary, this study describes the anti-fungal components in D. retusa extract, and our results provide a foundation for the study of their mechanism of action in this tree species.